Mekanisme Restrukturisasi Dalam Penyelesaian Pembiayaan Murabahah Bermasalah Pada Bank Sumut Syariah KC Medan Katamso - Afwan Hafizh; Nursantri Yanti (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The purpose of this study is to understand the restructuring mechanism in solving problematic murabahah financing at Bank Sumut Syariah KC Medan Katamso. This research uses descriptive qualitative method. The source of the data obtained and used in this study was obtained directly at the research location at PT Bank Sumut Syariah KC Medan Katamso. This study uses primary data. In addition, in this study, raw data was also collected in the form of secondary data, such as evidence, documents or historical reports, documents, archives, whether published or not. The data collection that the writer did was through observation, interviews and document studies. Observations were made through direct observation at PT Bank Sumut Syariah KC Medan Katamso. Interviews were addressed directly to the Business or Marketing division of PT. Bank Sumut Syariah KC Medan Katamso according to the information needs by answering the questions raised by the author. Document research conducted by the author is in the form of written data or other documents needed by the author. After doing the research, it can be concluded that the North Sumatra Sharia KC Medan Katamso Bank in implementing the restructuring mechanism there are principles that must be followed in resolving problem financing contained in Bank Indonesia Regulations and can be said to be good. The principles applied by Bank Sumut Syariah KC Medan Katamso are in accordance with Bank Indonesia Regulation No. 13/9/PBI/2011 concerning amendments to Bank Indonesia Regulation Number 10/1/PBI/2008 concerning Financing Restructuring for Sharia Banks and UUS. Namely, rescheduling, reconditioning, and restructuring.